Meet you at the crossroads: the simulation analysis of an airport for identifying potential problems - Mujica Mota, Miguel (2017)
The aeronautical industry is still under expansion in spite of the problems it is facing due to the increase in oil prices, limited capacity, and novel regulations. For this reason, it is necessary to have tools that help during the process of an expansion project, or during planning phases of new aeronautical infrastructures. For the particular case of a new airport project there are many variables to consider in order to minimize the risk of high costs or even serious problems during the operation of a new airport. The article presents a methodology that combines two simulation approaches that complement each other applied to the problem of the development of a new airport in The Netherlands. The use of the methodology gives light to the future problems that might be faced by the managers of the airport. One model focuses in the operative of the airport from a high-level angle taking into account the configurations that might be in place once the airport is under operation. The second model put focus in other technical aspects of the operation for challenging the feasibility of the proposed configurations and for identifying other issues that cannot be perceived with the first model. With the use of the methodology different problems and performance indicators can be foreseen and act in consequence. The combination of both approaches is a powerful one in which the overlapping of solutions will save a lot of money to the airport operators and/or airport developers.